(untitled) (Research, Society and Development, 2025)
Stella do Patrocínio was a poor black woman who lived institutionalized in mental hospitals for 30 years. In 2001, with the publication of her speeches, which were transcribed into poems, Patrocínio became a poet whose work conveyed intense accounts of her life and feelings in the Colônia Juliano Moreira mental hospital. Based on this author, this study aims to analyze the formation of mental hospitals, examining the historical process that established eugenics as a social and scientific ideology in Brazil- and Latin America -primarily during the Old Republic. It aims to demonstrate that this ideology is established through the precepts of mental hygiene, aiming to combat social degeneration and safeguard the model of the ’ideal citizen’- white, wealthy, heterosexual, and male. Thus, people who did not fit this pattern were considered ’maladjusted’ and ’dangerous’, and therefore abandoned by the State’s power mechanisms in mental institutions, where relationships are mediated by violence, abuse and torture, as Stella do Patrocínio’s speeches demonstrate.